Desenvolvimento rural e políticas públicas em assentamentos rurais: estudo de caso na Fazenda Monte Alegre SP - Santos, Arlei Rosa dos (2017)
This dissertation presents an analysis about rural development and public policies in Fazenda Monte Alegre settlement, located in the municipalities of Araraquara and Motuca in the state of São Paulo. For the analysis about rural development the population, economic, social and environmental dimensions were discussed, discussing the relationship with the public policies necessary for this development. The study was carried out based on bibliographical and documentary research. The bibliographic research was carried out using the technique of research in the state of the art, searching the scientific articles published in indexed journals and that dealt with the themes addressed in the study. The documentary research used data from the Land Institute of the State of São Paulo (ITESP) about the Fazenda Monte Alegre Settlement in the period of 2011-2014. Based on the analysis carried out, it is verified that the rural development in Fazenda Monte Alegre Settlement is directly related to public policies. In other words, the dimensions that have characteristics of rural development are those in which public policies are present. Thus, investments are required by the Government to guarantee rural development in all areas of rural agrarian reform settlements.